1992
DOI: 10.1037/0022-3514.63.6.932
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mothers' gender-role stereotypic beliefs on mothers' and children's ability perceptions.

Abstract: The focus of this study is the relation between mothers' gender stereotypic beliefs, their perceptions of their children's abilities, and their children's self-perceptions in 3 activity domains. Approximately 1,500 mothers and their 11- to 12-year-old children responded to questions about the children's abilities in the math, sports, and social domains. It was predicted that mothers' beliefs about their children would be moderated by their gender stereotypic beliefs about the abilities of female and male peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
283
0
30

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(338 citation statements)
references
References 67 publications
(125 reference statements)
20
283
0
30
Order By: Relevance
“…However, more recent scholarship has highlighted the role of family factors in mathematical aptitude (Casad et al 2015;Entwisle et al 1994;Frome and Eccles 1998), an influence that had been noted in some early research as well (Benbow and Stanley 1980;Block 1983). Parents' gender ideologies influence their children's self-confidence with respect to math (Muller 1998), and parents with traditional gender attitudes tend to have daughters with diminished mathematical self-efficacy (Frome and Eccles 1998;Jacobs and Eccles 1992;Jacobs 1991;Parsons et al 1982;Schafer and Gray 1981). Parents with lower mathematical expectations for their daughters tend to have daughters with less ambition in math (Casad et al 2015;Frome and Eccles 1998;Parsons et al 1982).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, more recent scholarship has highlighted the role of family factors in mathematical aptitude (Casad et al 2015;Entwisle et al 1994;Frome and Eccles 1998), an influence that had been noted in some early research as well (Benbow and Stanley 1980;Block 1983). Parents' gender ideologies influence their children's self-confidence with respect to math (Muller 1998), and parents with traditional gender attitudes tend to have daughters with diminished mathematical self-efficacy (Frome and Eccles 1998;Jacobs and Eccles 1992;Jacobs 1991;Parsons et al 1982;Schafer and Gray 1981). Parents with lower mathematical expectations for their daughters tend to have daughters with less ambition in math (Casad et al 2015;Frome and Eccles 1998;Parsons et al 1982).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings indicate that parental expectations do not have a significant impact on the gender math gap. However, Tiedemann (2000) and Jacobs and Eccles (1992) provide evidence t hat parents' gender stereotyped beliefs about their children's competence in ma.th (i.e. ma.th is a. male domain) influence children's self-perceptions of ability in ma.th and hence their ma.th achievement.…”
Section: 1 Factors Influe Ncing Gender Test Score Gap: N Ature Versumentioning
confidence: 99%
“…They may be more attracted to activities where they think they can succeed rather than to new, and more daring, activities (see Eccles, 1994Eccles, , 2010Jacobs andEccles, 1992: Jussim andDiekman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, without women role models for success in male-dominated domains, female stereotypes persist (Jacobs and Eccles, 1992;Jussim and Eccles, 1992;Diekman et al, 2010). However, a Swedish survey (NUTEK, 2003), which notes the androcentric perspective of many research studies, found that an analysis of industry sectors is very relevant in the analysis of women and men at work.…”
Section: Women and Men At Workmentioning
confidence: 99%